2022
DOI: 10.3390/ani12101315
|View full text |Cite
|
Sign up to set email alerts
|

Live Yeast Supplementation in Gestating and Lactating Primiparous Sows Improves Immune Response in Dams and Their Progeny

Abstract: The present study determined the effects of live yeast (LY) supplementation during middle–late gestation and the lactation period in primiparous sows on reproductive parameters, lactation performance, and immunity, and also explores the carryover effects in their offspring. On day (d) 60 of gestation, 16 crossbred primiparous sows were randomly assigned to two dietary treatments (with or without supplementation of 425 mg/kg of live yeast; LYT and CT, respectively) homogeneous for body weight (BW) and backfat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…IgM is a vital anti-inflammatory component and elevated IgM content indicates better immunity [59]. The increased concentration of IgG is also reflected in a better immunological response and health for the lactating sows [60]. The increase in serum IgG and IgM concentrations elicited by ETEC invasion in our study might help eliminate invaders and neutralize toxins through specific binding with corresponding antigens in humoral immunity [61].…”
Section: Discussionmentioning
confidence: 61%
“…IgM is a vital anti-inflammatory component and elevated IgM content indicates better immunity [59]. The increased concentration of IgG is also reflected in a better immunological response and health for the lactating sows [60]. The increase in serum IgG and IgM concentrations elicited by ETEC invasion in our study might help eliminate invaders and neutralize toxins through specific binding with corresponding antigens in humoral immunity [61].…”
Section: Discussionmentioning
confidence: 61%
“…Some authors have attributed the ability of yeast-based products to provide reproductive benefits due to the predisposition towards a higher feed intake [ 27 , 29 ], increasing the average daily intake [ 5 , 27 ] and improving the feed efficiency of pigs [ 5 ]. Studies conducted using fermentation products obtained from Saccharomyces cerevisiae and administered to sows during gestation and lactation have shown that the benefit is the weight gain of the litter during lactation [ 12 , 13 , 16 ] and the improved immunological status of both the mother and the litter [ 30 ]. The present study failed in finding those latter differences between the two experimental groups, while there was a reduced mortality of suckling piglets and a tendency to have a higher average weight at birth in the treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Even if, in the present study, the postbiotic was administered only to the mother, some authors suggest that the modulation of the maternal gut microbiota after a postbiotic administration might be later transferred to the offspring. For example, Xia et al [ 30 ] found a reduced diarrhea incidence in piglets weaned from mothers previously fed with Saccharomyces cerevisae. Similar results were also reported by Betancur et al [ 35 ] in lactating piglets.…”
Section: Discussionmentioning
confidence: 99%
“…As the current goal of including probiotics in livestock diets is to act as replacements for antibiotics, enhancing lymphocyte subsets that drive antibody production may be advantageous. Xia et al [29], when feeding a live yeast probiotic to the dam during gestation and lactation, discovered that offspring from those treated sows had elevated concentrations of IgG and IgA at birth and well into the post-wean period. Higher levels of these two immunoglobulins may indicate an improved functionality of the adaptive immune response to fight off infection, as more antibodies are readily available to bind and begin to fight off the infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, utilizing probiotics during gestation and lactation to program offspring's immune function may prove more economically friendly than supplementing piglets individually. Xia et al [29] illustrated that including S. cerevisiae in maternal diets at gestation and lactation altered serum immunoglobulin concentration of the progeny post-wean; however, the effects of Scb and other immune measures are unknown. Thus, this study aimed to determine if maternal supplementation of Saccharomyces cerevisiae var.…”
Section: Introductionmentioning
confidence: 99%